Internship report : an analysis of the structure and practice of information technology professional development in Essex County, England - Tracey, William F., 1965- (1997)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1997. Education Bibliography: leaves 70-73 The research component of this internship was designed to ascertain the nature of inservice training with respect to Information Technology ( IT ) within Essex County, England. -- There were four criteria which were examined, first, through literature review, and then, evaluated during the internship period. These criteria were the impetus of Information Technology inservice training, the focus of Information Technology inservice training, the situation or place of Information Technology inservice training and follow up to Information Technology inservice training. -- This research study sought to identify whether the principles and the practices of Information Technology professional development inservice in Essex County tended to support or to repudiate literature findings. The above four criteria for Information Technology inservice were examined utilizing Essex County Education policy documents and through researcher observation. -- The principles and practices for Information Technology inservice in Essex County tended to agree with literature findings on the four criteria. Factors such as competitiveness between schools and decision-making power remaining in the hands of school governors, according to this researcher, may still have played a significant role in the information technology inservice process.